Frequency And Type Of Refractive Errors Among The Teenage Groups Presenting In Eye OPD In Shaikh Zayed Hospital Lahore - Sumaira Rahim; Irum Abbas; Atif Mansoor Ahmed; Zyiemah Arif; Abdul Qudos; Tehmina Imdad (Journal of Rawalpindi Medical College)
Objective: To determine the frequency and type of refractive errors in the teenage groups reporting in ophthalmology department of Shaikh Zayed Hospital Lahore, Pakistan.